Interview with Dr. Mary Grantham O’Brien: Looking at comprehensibility as a dynamic construct - Teló, Cesar; O’Brien, Mary Grantham (Revista X, 2021)
In this interview, Dr. Mary Grantham O’Brien, from the University of Calgary, discusses the notion of comprehensibility as a dynamic—rather than static—dimension of L2 speech.